Proposed New Line Business Development for CV. Tiga Berlian - ., Hilaluddin; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2017)
Abstract : CV. Tiga Berlian is business engaged in the field of waste management the industrial products. CV. Tiga Berlian is established by Mr H. Dofir in 2003. The problems faced by CV. Tiga Berlian is increasingly local competition in business waste management the industrial products and also is focused on industrial waste management innocuous (non-hazardous waste), while the industry produced not only non-hazardous waste but also hazardous waste. It affects the business of CV. Tiga Berlian in terms of corporate income and the number of companies in cooperation with CV. Tiga Berlian. In exploration business, writer was using internal and external analysis to find strengths, weaknesses,  opportunities and threats. For external analysis was using PESTEL analysis and Porter’s Five Forces analysis. While, for internal analysis was using existing Business Model Canvas and Corporate Value Chain. Mean while, strategy formulation was using TOWS matrix and Business Model Canvas. The results of the analysis showed there were high competition in the business, and weakness in management. The strategy that can be applied for improving company management were focusing on efficiency, and implementing integrated management service. For facing high competition in short-term the company should be improving the management system, including financial system and team work management. In medium-term the company should be developed networks, and equipped licensing Hazardous waste. In long-term the company should open a centre of new business development in waste management for Hazardous waste, including hospital waste, and transportation services for hazardous waste. Keywords : PESTEL analysis, Porter’s five force Analysis, Matriks TOWS, SWOT analysis